Fluconazole Alters the Polysaccharide Capsule of Cryptococcus gattii and Leads to Distinct Behaviors in Murine Cryptococcosis - Santos, Julliana Ribeiro Alves; Holanda, Rodrigo Assunção; Frases, Susana; Bravim, Mayara; Araujo, Glauber de S.; Santos, Patrícia Campi; Costa, Marliete Carvalho; Ribeiro, Maira Juliana Andrade; Ferreira, Gabriella Freitas; Baltazar, Ludmila Matos; Miranda, Aline Silva; Oliveira, Danilo Bretas; et al. (PLOS ONE, 2014)
Cryptococcus gattii is an emergent human pathogen. Fluconazole is commonly used for treatment of cryptococcosis, but the emergence of less susceptible strains to this azole is a global problem and also the data regarding fluconazole-resistant cryptococcosis are scarce. We evaluate the influence of fluconazole on murine cryptococcosis and whether this azole alters the polysaccharide (PS) from cryptococcal cells. L27/01 strain of C. gattii was cultivated in high fluconazole concentrations and developed decreased drug susceptibility. This phenotype was named L27/01F, that was less virulent than L27/01 in mice. The physical, structural and electrophoretic properties of the PS capsule of L27/01F were altered by fluconazole. L27/01F presented lower antiphagocytic properties and reduced survival inside macrophages. The L27/01F did not affect the central nervous system, while the effect in brain caused by L27/01 strain began after only 12 hours. Mice infected with L27/01F presented lower production of the pro-inflammatory cytokines, with increased cellular recruitment in the lungs and severe pulmonary disease. The behavioral alterations were affected by L27/01, but no effects were detected after infection with L27/01F. Our results suggest that stress to fluconazole alters the capsule of C. gattii and influences the clinical manifestations of cryptococcosis.